Association of Southeast Asian Nations, People's Republic of China, and India growth and the rest of the world: The role of trade - Robert Z. Lawrence (Asian Development Bank Institute (ADBI), 2013)
This paper explores the impact of past and future growth in the Association of Southeast Asian Nations (ASEAN)1 Since the mid-1990s, ACI growth has improved the non-oil terms of trade of the developed countries. There have also been strong complementarities between ACI suppliers of intermediate inputs and PRC exports. More developed Asian countries have benefited from PRC capital goods demand. ACI growth has, however, put competitive pressures on other less-developed manufacturing exporters, worsening their terms of trade and constraining their pricing ability. ACI growth has been especially beneficial for oil and minerals commodity producers. On the other hand, net food importers and oil importing countries have been adversely affected by high import costs. , the People's Republic of China (PRC), and India - here referred to as the ACI countries - on aggregate welfare, relative wages, and global emissions in the rest of the world. It outlines several analytical frameworks, considers effects over the past decade and, based on consensus forecasts, the implications of that growth for the rest of the world in the decades to come. Future ACI growth provides opportunities and challenges for the rest of the world. For developed countries the opportunities are for selling high-end services and capital and consumer goods in the ACI markets and enjoying the benefits from intra-industry trade; the challenges will come from increased head-to-head competition in manufactured goods and services that should become more intense in future decades. For medium-income producers currently at between 30% and 60% of US levels, there will be a tougher tradeoff between more intensive competition with the PRC and serving the growing middle classes in ACI countries. For poorer countries, there will greater opportunities for becoming part of global supply chains in manufactured exports. Standard frameworks that assume internal factor mobility suggest continuing pressures for wage inequality in developed countries. But these hinge on the assumption that the ACI and developed countries will continue to produce similar products and that the ACI will specialize in unskilled labor-intensive products. In fact, as their exports become more technology - intensive and developed countries more specialized these pressures could be alleviated. On the one hand, as the "flying geese" process continues, exports from countries with lower incomes than the PRC are likely to displace PRC labor-intensive exports rather than domestic production in developed countries. On the other hand, while it may cause job loss and erode the returns to specific factors, PRC export growth is less likely to be a source of wage inequality in advanced economies.
Keywords: F01; F10; 330; asean; prc; trade; economic growth; aggregate welfare; relative wages; and global emissions; Internationale Arbeitsteilung; Handelsliberalisierung; Wirtschaftswachstum; China; Indien; ASEAN-Staaten